2005
DOI: 10.1002/app.21662
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube core–polymer shell nanofibers

Abstract: Single-walled carbon nanotube (SWNT)/ poly(methyl methacrylate) and SWNT/polyacrylonitrile composite nanofibers were electrospun with SWNT bundles as the cores and the polymers as the shells. This was a novel approach for processing core (carbon nanotube)-shell (polymer) nanofibers. Raman spectroscopy results show straininduced intensity variations in the SWNT radial breathing mode and an upshift in the tangential (G) and overtone of the disorder (GЈ) bands, suggesting compressive forces on the SWNTs in the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several factors such as the molecular weight of polymer, the concentration of solution, the flow rate of fluid, the strength of electric field, and the distance from the needle tip to the collector significantly influenced the size and morphology of the resultant fibers. In this work, PAN and PANCMPCs with different MPC contents were synthesized by a waterphase precipitation copolymerization process and then electrospun into nanofibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several factors such as the molecular weight of polymer, the concentration of solution, the flow rate of fluid, the strength of electric field, and the distance from the needle tip to the collector significantly influenced the size and morphology of the resultant fibers. In this work, PAN and PANCMPCs with different MPC contents were synthesized by a waterphase precipitation copolymerization process and then electrospun into nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Among various polymers, acrylonitrile-based homopolymers and copolymers were most recently fabricated into nanofibrous materials with reinforcing superhydrophobic and/or catalytic properties. [6a,9-20] In our previous work, novel nanofibers possessing reactive carboxyl groups were fabricated from poly[acrylonitrile-co-(maleic acid)] and poly[acrylonitrile-co-(acrylic acid)] by the electrospinning process.…”
Section: Introductionmentioning
confidence: 99%
“…This includes a thorough understanding of the structure-property relationship for various electrospun polymer nanofibres, the effective incorporation of carbon nanotubes into polymer fibres with a high loading content, and large scale production of composite nanofibres of consistent and high quality but at a low cost [164] [165] [166]. Core-shell CNT/polymer nanofibres are also a subject that warrant further research [167].…”
Section: Discussionmentioning
confidence: 99%
“…By addition of 20 wt% to three di erent ceramic nanoparticles, namely Calcium Titanate (CT), Strontium Titanate (ST), and Barium Titanate (BT), Bagchi et al signi cantly increased the moduli and strength of poly(" caprolactone) [38]. In this context, a large number of other studies have shown that MWNTs, with low percentages, can signi cantly improve the mechanical properties of di erent polymers [39][40][41][42][43][44][45][46]. Li et al prepared the MWNT/ poly(3-hydroxybutyrate-co-3-hydroxyvalerate) sca olds by Melt Molding method, and reported that MWNTs can signi cantly improve the mechanical properties of the polymer [47].…”
Section: Introductionmentioning
confidence: 99%